Foreign Direct Investment from India and China to Nepal: Trends and Sectoral Insights - K C, Sunder; Nepal, Pramshu (International Research Journal of Parroha, 2025)
Foreign direct investment (FDI) is a vital driver of economic growth and development in Nepal, bridging gaps in capital, technology, skills, and entrepreneurship. This study examines the trends of FDI inflows from India and China to Nepal, highlighting their sectoral composition, historical context, and economic significance. India remains the largest FDI provider, primarily investing in manufacturing, electricity, and financial services, while China’s FDI is concentrated in electricity and manufacturing sectors. Despite Nepal’s investment-friendly policies, such as FITTA 1992 and FITTA 2019, actual FDI inflows often lag behind approved amounts due to political instability, bureaucratic inefficiencies, infrastructural bottlenecks, corruption, restrictive labor laws, and societal perceptions of capitalism. This descriptive study uses secondary data from Nepal Rastra Bank, government agencies, and international reports to present a comprehensive analysis of trends, sectoral engagement, and challenges. The findings underscore opportunities for policy reforms and strengthened bilateral relations to enhance FDI inflows, ensuring sustainable economic development in Nepal.